Overview of Research Methods for Shear Lag Effect of LVL-UHPC Composite Box Girder - Liao, Yuanyuan (International Core Journal of Engineering, 2026)
In the development and application of bridges, box section is the most common section used in bridges, mainly because the box section bridge has good mechanical performance and stiffness. Although the good mechanical performance of box girder structure is outstanding, it must be considered in the design of engineering structure because of the existence of shear lag. Otherwise, it is easy to have safety accidents, and many accidents of tube structures and bridges are caused by shear lag. Therefore, strengthening the research on shear lag of box-section structural system is not only the need of the development of civil engineering analysis theory, but also has important practical significance and application value.